Do ser genético ao ser afetivo: a ontologia do ser na mediação Waratiana - Tosi, Sandra Cristina (Universidade do Vale do Rio dos Sinos, 2012)
This research addresses the theme of man as a being who lives and shares different worlds, looking for his evaluative preferences, his tastes and skills. As a result, he needs to link affectively, be recognised and valued, so he can be in harmony with each other and with himself. Love, in this context, reflects in the communication guideline between human beings, in a way that the right of loving and being happy means a duty to understand and be with each other, because, only in this way, there is a break with the individuality and preconceptions. The conflict is a human being inherent element, which acts by stimulating his interest and his curiosity, removing him from his natural comfort zone, to provide him conditions for promoting individual and social changes, because, once understood, the conflict has the power to become a life transformation instrument. It is true, however, that on a Democratic State of law, a conflict born of society is governed and treated in the Judiciary, where is reduced to a dispute figure, in which the State-Judge applies the law by case. Thus, before the attempt to act on the conflict, rather than act on people’s feelings, the conflict never disappears, just changes itself. This research proposes to find out a solution or alternative treatment for conflict resolution, analyzing the State traditional way of acting in confrontation with the mediation institute as an alterity ethics. For these reasons, it will be held a re-reading of mediation as an environmentally-friendly way of social and legal conflict resolution, allowing the communication re-establishment between opponents, under the Waratiana design. Mediation is the art of more listening than talking. This study is justified on the need of getting a contemporary vision of the Justice idea, investigating the Law effectiveness and the mediation applicability in preventing and resolving disputes through consensus. The method used is the phenomenological as interpretation, to make a reflection on the human being and its controversial social relations, and, also, analyze the problems that arises on this alternative model of justice based on consensus built among opponents through communication. In Luis Alberto Warat’s vision, mediation can be used as an instrument of conflict dissolution in different areas of society, from family conflict, through the humanities, until institutional and community conflicts in their most varied types. To achieve this, it is necessary an urgent change in the solutions or transformation conflict system, in order to deconstruct the Jurists theoretical common sense, because, more than the decision itself pure and cold, the conflict solution must achieve a better life quality for people in it involved.
Keywords: Homem; Afeto; Conflito; Consenso; Mediação; Man; Affection; Conflict; Consensus; Mediation; ACCNPQ::Ciências Sociais Aplicadas::Direito